How Forced Displacements Caused by a Violent Conflict Affect Wages in Colombia - J. Ignacio Gimenez-Nadal; José Alberto Molina; Edgar Silva Quintero (Institute for the Study of Labor (IZA), 2016)
In this paper, we analyze how forced displacements caused by violent conflicts affect the wages of displaced workers in Colombia, a country characterized by a long historical prevalence of violent conflicts between the government, the militia group (FARC), drug trafficking, and other crime that affect hundreds of people, forcibly displaced to other regions of the country. Using data from the Quality of Life Survey (2011-2014), we analyze differences in wages between those who were forced to move to other regions, and those who were not forced to move. In our empirical strategy, we take into account that those who were displaced may have characteristics that differ from those who were not forced, and we apply Propensity Score Matching techniques to consider forced displacements exogenous to the individuals. We apply different matching algorithms, and find that forced displacement decreases between 6% and the 22% the wages of males, and between 17% and 37% the wages of females, compared to their non-displaced counterparts. Thus, forced displacements result in poorer labor market outcomes, and the government should explore how public policies may help to alleviate the negative consequences of forced displacements as first step to reduce wage inequalities originated by these conflicts.
Keywords: J15; J31; R23; 330; forced displacement; wages; Propensity Score Matching; Colombia